Perancangan Sistem Pendeteksi Pencurian Bahan Bakar Kendaraan Berbasis Arduino - Alfa Satya Putra; Jennifer Novia Nursalim; Arnold Aribowo; Hendra Tjahyadi (Jurnal Teknologi Informasi dan Pendidikan, 2020)
Fuel shortage is a common problem in Indonesia. This prompted many cases of vehicle fuel theft. As a solution to this problem, an Arduino-based vehicle fuel theft detector system is implemented. Arduino-based vehicle fuel theft detector system is a prototype that uses Arduino UNO as a microcontroller, IComSat v1.1 SIM900 GSM/GPRS Shield to communicate with mobile phone, fuel level sensor as a volume detector, and push button as a detector to check whether the fuel tank’s lid is open or closed. The working principle of this system is to detect the state of the fuel tank lid. When the lid is open, the system will make a phone call. Then, the system will keep track of fuel volume. If there is a drastic decrease in volume, the system will send information about the decreasing volume in the form of a short message to the owner of the vehicle. The success rate of the communication system between Arduino UNO and other electronic devices is 100%. Accuracy of fuel level sensor is 90%. Success rate of push button switch in detecting the state of fuel tank’s lid is 100%. Success rate of GSM Shield communication is 90%.